Modern Aspects of the Use of Computer-Assisted External Fixation Devices (Literature Review) - Suvorov, V.L.; Yevlantieva, T.A.; Kulyk, Yu.A.; Kozik, Ye.V.; Larkevych, O.H.; Demian, Yu.Yu. (TERRA ORTHOPAEDICA, 2025)
Summary. The use of computer-assisted external fixation devices (CAEF) is an effective and minimally invasive method for correcting multiplanar deformities and bone defects in both children and adults. They allow for a higher degree of correction compared to the classic Ilizarov apparatus, while reducing the incidence of complications. Among the most effective CAEF systems are the Taylor Spatial Frame (TSF) and the Orthex Hexapod System. Additionally, the robotic Auto Strut system demonstrates high correction accuracy with minimized errors. The most common complications associated with CAEF use include superficial infections, temporary joint contractures, and delayed consolidation, which are generally managed conservatively.